2021
DOI: 10.1590/interface.200208
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento humano e formação interdisciplinar: possibilidades de encontro entre os cursos de Psicologia e Terapia Ocupacional

Abstract: Este artigo tem por objetivo relatar uma experiência de formação interdisciplinar por meio de possibilidades de encontro entre os cursos de Psicologia e de Terapia Ocupacional (TO) acerca do desenvolvimento humano. O relato prioriza a dinâmica de aproximação entre duas disciplinas, o planejamento, as estratégias e a avaliação do conteúdo. Essa experiência evidenciou possíveis encontros que se abrem com a proposta da interdisciplinaridade no ensino. Por intermédio do planejamento interconectado e de propostas d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 14 publications
0
3
0
2
Order By: Relevance
“…Interdisciplinary and interprofessional teaching is highlighted as an important assumption in consolidating this training. From this perspective, the challenge is to bring together actors (teachers, students, professionals) from different areas in the same space, providing partnerships to consolidate interactive and cooperative learning (Castro et al, 2016;Capozzolo et al, 2018;Silva & Borba, 2018;Panciera et al, 2021;Carvalho et al, 2020b;Chriguer, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interdisciplinary and interprofessional teaching is highlighted as an important assumption in consolidating this training. From this perspective, the challenge is to bring together actors (teachers, students, professionals) from different areas in the same space, providing partnerships to consolidate interactive and cooperative learning (Castro et al, 2016;Capozzolo et al, 2018;Silva & Borba, 2018;Panciera et al, 2021;Carvalho et al, 2020b;Chriguer, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Playful workshops in schools, beaches and youth centers (Panciera et al, 2021) and difference workshops (Silva & Borba, 2018) are also described. The latter was conceived as meetings aimed at triggering reflections that express the multiplicity of youth Publications by Palm (2014), Baldani (2016) and Alonso et al (2021) indicate that the strategies found within the scope of mental health teaching reveal the predominance of teaching-learning methods supported by the problematization and contextualization of reality, with training in context, dialogue and interaction with the various points of the Care Network being important.…”
Section: What Are the Pedagogical Strategies And Who Teaches?mentioning
confidence: 99%
See 1 more Smart Citation
“…O ensino interdisciplinar e interprofissional está destacado como pressuposto importante na consolidação dessa formação. Nessa perspectiva, o desafio está em reunir atores (docentes, estudantes, profissionais) de diferentes áreas em um mesmo espaço, proporcionando parcerias para sedimentar aprendizagens interativas e cooperativas (Castro et al, 2016;Capozzolo et al, 2018;Silva & Borba, 2018;Panciera et al, 2021;Carvalho et al, 2020b;Chriguer, 2022).…”
Section: Discussão O Que é O Ensino Territorial E Comunitário?unclassified
“…Estão descritas, ainda, oficinas lúdicas em escolas, praias e centros da juventude (Panciera et al, 2021) e oficinas da diferença (Silva & Borba, 2018). Essa última concebida como encontros voltados a disparar reflexões que expressem a multiplicidade de experiências juvenis.…”
Section: Quais As Estratégias Pedagógicas E Quem Ensina?unclassified